PENGARUH BIMBINGAN KELOMPOK TERHADAP PENINGKATAN PERENCANAAN KARIR SISWA KELAS X MIA SMA NEGERI 12 PEKANBARU TAHUN PELAJARAN 2014/2015 - Umari, Tri Umari; ', Jejaka; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aims to determine the effect of the increase in group counseling career planning class X Mia SMA 12 pekanbaru school year 2014/2015. This research was conducted in SMA 12 months Pekanbaru from March 2015 to May 2015. The method used was experimental method to pattern one-group pretest-posttest.Populasi all students career planning is low and 30 of the population sampled (purposive sampling) Instruments Data collection was a questionnaire using Guttman scale for the dependent variable: Improved Career Planning (Y). Data analysis technique used is the statistical correlation techniques. The result showed that group counseling is partially an effect on career planning MIA students of class X SMA Negeri 12 Pekanbaru school year 2014/2015. This is based on the results of analyzes, calculations show thitung> ttable (11.27> 2,000). So it can be concluded that guidance on career planning influential group of students with a contribution of 40% while 60% is influenced by factors - other factors contained in the students themselves and the environment. Key Words : Effect Of Group Counseling , Career Planning .